Mengidentifikasi keanekaragaman Hewan Invertebrata di Pesisir Pantai Sarae Me’e Desa Tolotangga Kecematan Monta - Pipit Fadillah; Sri Julita Winata; Nilam Terpuji; Nurjanah; Sukarni (JUSTER : Jurnal Sains dan Terapan, 2024)
Invertebrates are a large group of living creatures that do not have backbones. In biological classification, these animals include various groups such as arthropoda, mollusca, annelida, and echinodermata. Even without backbones, invertebrates have various body suppart systems, such as exoskeletons or internal skeletons. The study of invertebrtes not only illustrates their morphological divetsity, but also shows their crucial role in ecosystems as pollinators, decomposers, and food sources.and 97% of species in the world are invertebrates. This research activity is an activity that aims to identify data about the types of invertebrate animals that exist on Sarae Me’e beach, Sarae Me’e Beach is an open sea type beach, causing the waves on the beach to be large. This research was carried out on January 3 2024. The method used in this research is the exploration and identification method using exploration techniques along the coastline. The research objects are Invertebrate animals found along the coast of sarae me’e, Tolotangga village, Monta subdistrict. The data analysis technique used in this research is descriptive analysis technique. The results of the research faund four Invertebrate animals including the phylum Mollusca, Gastropoda, Athropoda and Annelida.and the salinity condition of the waterthat we tested using a salinity tool was 30% salt content on Sarae Me’e when we conducted the research.